Kerala's Democratic Decentralisation: History in the Making - SHOBHA RAGHURAM (Economic and Political Weekly June 17, 2000, 2000)
The democratic decentralisation campaign in Kerala is of unique significance in the history of India for it establishes a politics of social change which restructures the systems of power, of production and of relations, especially between state, governmentand people who image the alternatives and build them. Impressions of the State Planning Board's International Conference on Democratic Decentralisation last month.